The importance of tissue fixation for light microscopic immunohistochemical localization of peroxisomal proteins: the superiority of Carnoy's fixative over Baker's formalin and Bouin's solution - Lehmann, Thorsten G.; Völkl, Alfred; Fahimi, H. Dariush (Histochemistry and cell biology, 1995)
We have compared the effects of fixation with three commonly used fixatives upon preservation of the antigenicity of six peroxisomal proteins in rat liver using both immunohistochemical staining and Western blotting of fixed tissue extracts. The immunoreactivity of all six peroxisomal proteins was well preserved and peroxisomes were clearly identified in material fixed in Carnoy's fixative. Moreover, the corresponding proteins stained well in Western blots prepared from extracts of Carnoyfixed material. The intensity of the immunohistochemical staining was reduced at different rates for individual peroxisomal proteins after fixation in Baker's formalin, but peroxisomes were still well visualized with antibodies to catalase and some β-oxidation enzymes. No evidence of immunohistochemical staining for any peroxisomal antigens was obtained after fixation in Bouin's fluid. For detection of the antibody binding sites in Carnoy's fixed material, the avidin-biotin-peroxidase complex (ABC) with aminoethyl carbazole as chromogen was found to be superior to the methods of peroxidase-antiperoxidase/diaminobenzidine and protein A-gold with silver intensification. Using Carnoy-fixative and the ABC-method, we demonstrate light microscopic immunohistochemical localization of peroxisomal antigens in several rat tissues as well as in human post-mortem liver.